Trend and spatial pattern of intimate partner rape notifications against women in Northeast Brazil (2013-2022) - Marília Ramalho Oliveira; Alberto Pereira Madeiro; Fernando Ferraz Nascimento; Jesusmar Ximenes Andrade; Malvina Thais Pacheco Rodrigues; Márcio Dênis Medeiros Mascarenhas (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2024)
ABSTRACT Objective: To analyze the trend and spatial pattern of intimate partner rape reports against women in Northeast Brazil. Methods: Ecological time-series study and spatial analysis with secondary data from the Notifiable Diseases Information System between 2013 and 2022. Gross rape rates were calculated by type of intimate partner and by age group of the victim. Prais-Winsten regression was used to calculate the trend, and the global and local Moran indices were used for spatial analysis. Results: A total of 5,542 cases of intimate partner rape were reported. Spousal rates ranged from 0.34/100,000 women in 2013 to 0.51/100,000 in 2017, with greater increases between 2018 (1.04/100 thousand) and 2022 (1.28/100 thousand). There was an upward trend in the Northeast as a whole (APC=19.47; 95%CI 15.88-23.22) and in almost all states, except Paraíba and Sergipe. Cases perpetrated by boyfriends (APC=23.90; 95%CI 12.80-36.09) and among women aged 15 to 19 years (APC=22.63; 95%CI 4.18-44.35) showed the highest annual variation. A concentration of high rates was observed in several municipalities in the northwest of Ceará and southeast of Pernambuco. Conclusion: The trend in intimate partner rape rates against women increased in the Northeast, especially among younger women and by boyfriends, with a greater agglomeration of notifications in Ceará and Pernambuco.